Defining Paradigms for Effective Industry Institute Collaboration - Chavan, Ameet; Sanapala, Bhujanga Rao (Journal of Engineering Education Transformations, 2015)
Low employability and poor quality of today’s graduating engineers is the issue of huge concern for sustaining the economic growth and country’s progress. Both the issues have arisen due to an existing gap in acquiring necessary technical skills by the engineers, which are required by the hiring industry. This problem has to be addressed by the synergetic efforts of the institutes and industries - two entities which play the vital role of supply and demand. For enabling a bright future to the next generation it is important that this association is more effective with active collaboration. The paper makes an earnest effort in suggesting and identifying the key areas for industry-institute collaboration.